2018
DOI: 10.1080/02670836.2018.1463614
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in the high-cycle fatigue behaviour of γ-TiAl alloys

Abstract: The high-cycle fatigue (HCF) properties of γ -TiAl (gamma titanium aluminide) alloys are reviewed, particularly with regards to the deformation mechanisms active in the near-threshold cyclic loading regime. By examining the influence of lamellar orientation and thickness on the HCF threshold, in addition to more conventional microstructural considerations such as the grain size or the volume fraction of lamellar colonies, factors to improve the γ -TiAl microstructure for HCF are assessed. Finally, experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 145 publications
2
22
0
Order By: Relevance
“…Instead, here, at both 25 ºC and 700 ºC, such localised plasticity, identified in microcompression samples by a combination of DIC and TEM, was attributed to longitudinal slip occurring 30 -50 nm away from lamellar interfaces, and longitudinal twinning propagating from the interfaces, without cracking. These two latter deformation mechanisms maintain material cohesion and may produce equivalent surface steps as previously identified by AFM [6], have the same appearance in BSE imaging as the features reported to be microcracks and interfacial sliding [50], and, furthermore, microplasticity may generate acoustic emissions [51], similarly to microcracking, as remarked by Appel et al [46].…”
Section: Location Of Plasticity Occurring Below the General Yield Stresssupporting
confidence: 56%
“…Instead, here, at both 25 ºC and 700 ºC, such localised plasticity, identified in microcompression samples by a combination of DIC and TEM, was attributed to longitudinal slip occurring 30 -50 nm away from lamellar interfaces, and longitudinal twinning propagating from the interfaces, without cracking. These two latter deformation mechanisms maintain material cohesion and may produce equivalent surface steps as previously identified by AFM [6], have the same appearance in BSE imaging as the features reported to be microcracks and interfacial sliding [50], and, furthermore, microplasticity may generate acoustic emissions [51], similarly to microcracking, as remarked by Appel et al [46].…”
Section: Location Of Plasticity Occurring Below the General Yield Stresssupporting
confidence: 56%
“…The similar behavior of the two highest deformed conditions is attributed to their almost identical microstructure, as shown in Figure 1 c,d. At RT, the γ-phase is prone to micro-plastic deformation through dislocation movement [ 47 , 55 , 56 , 57 ]. The generated strain accumulation leads to crack initiation at the boundaries of the relatively soft and globular γ-grains [ 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The generated strain accumulation leads to crack initiation at the boundaries of the relatively soft and globular γ-grains [ 58 , 59 ]. Consequently, the coalescence of these early defects leads to the formation of a pre-crack at the grain boundaries, which propagates further by stable crack growth [ 56 , 58 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is important to investigate their fracture behavior during high-cycle fatigue (HCF) for improving the service property of TiAl alloys. Most of the previous researches have been focused on fatigue crack growth [12][13][14][15]. It was demonstrated that the low ductility and toughness of TiAl alloys result in a low tolerance to fatigue crack growth and a relatively steep slope of the Paris region [16,17].…”
Section: Introductionmentioning
confidence: 99%